Kajian Pendidikan Indonesia di Era Revolusi Industri 4.0: Kearifan Lokal dalam Perspektif Bimbingan dan Konseling: Study of Education in Indonesia in the Era of Industrial Revolution 4.0: Local Wisdom in Prespective of Guidance and Counseling - Amalia, Riza; Hidayah, Nur; Hotifah, Yuliati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The development of national education began after Indonesia’s independence day, and then the government gradually expanded national education, so that education in Indonesia has entered 3 eras, there was modern education, post-modern education, and millennial education. The most recent curriculum launched by the Ministry of Education and Culture is the Independent Curriculum during the Covid-19 pandemic. Essentially, we are required to follow the development of the era, but we must not abandon the foundations of Indonesian culture. Multicultural education based on local wisdom is a requirement that must be implemented, particularly in the field of guidance and counseling. Local wisdom has been established to improve good conditions for students at all levels of education. Research objective: to explain and describe the study of implementing education in the areas of guidance and counseling throughout the Industrial Revolution. Method: literature review by applying 7 steps of literature review by using collection information tools that as scientific literature search software. Results: The 10 journals determined that multicultural education based on local wisdom can increase positive aspects such as resilience, self-awareness, interpersonal communication, self-confidence, self-control, and self-openers when used in guidance and counseling services. Conclusion: In the industrial revolution age, local wisdom is significant and useful in applying guidance and counseling 4.0.